A grammatical sketch of Hainan Cham : history, contact, and phonology - Thurgood, Graham; Thurgood, Ela; Li, Fengxiang (Pacific linguistics, 2014)
"This volume is a grammatical sketch of Hainan Cham, an endangered tonal Austronesian language. The study focuses on three areas: social background and contact history, the grammar (including all the recorded vocabulary), and a description of the sound system (including acoustic description). The appendixes also include the wordlist of Sanya Chinese forms and four analyzed texts"--